Pemetaan Dan Analisis Tingkat Radiasi Gelombang Extremely Low Frequency (Elf) Pada Permukaan Bumi Tertentu Sebagai Suatu Pendekatan Ilmiah Terhadap Fenomena Paranormal (Studi Kasus Pada Tempat-Tempat Angker Di Kabupaten Alor) - Imanuel Christian Mauko; Robinson A Wadu; Nicodemus Mardanus Setiohardjo (P3M- Politeknik Negeri Kupang, 2020)
The existence of Extremely Low Frequency (ELF) waves in several places on earth, also influences the socio-cultural mindset of certain people who strongly believe in paranormal, superstitious and mystical stories about the existence of ghosts around them. One of the places known for its paranormal practice is the people who inhabit Alor Island in Alor Regency, East Nusa Tenggara, Indonesia. This paranormal phenomenon still cannot be explained logically, so that sometimes it causes complicated social problems in society, even the stikma of